Is COVID Revealing a Virus in CMBS 2.0? - GRIFFIN, JOHN M.; PRIEST, ALEX (Journal of Finance, 2023)
ABSTRACT Commercial loan valuations crucially depend on accurate loan income, but underwritten income on commercial mortgage‐backed securities (CMBS) loans is commonly overstated relative to actual property income. Consistent with these differences being originator‐specific, income overstatement in CMBS 2.0 deals varies widely and persistently across originators, is priced by originators, is related across property types within an originator, is predictable ex ante, and is accompanied by inflation of past financials. Risk retention and associated regulation had no discernible effect on income overstatement. Originator income overstatement is highly predictive of pre‐ and COVID‐period loan distress. Overall, recent market stresses reveal large systemic differences in underwriting standards across originators.